Learning to Philosophize as a Necessary Condition for Change in the World - Adam, Andrej (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
In this paper, we start from Marx’s eleventh thesis on Feuerbach: “Philosophers have only interpreted the world in various ways; the point, however, is to change it.” We argue that the pursuit of philosophy for such change has become necessary: philosophizing is an essential part of such change because it implies opposition to constant adaptation to the circumstances required by economics. In this light, the work of Rudi Kotnik is part of the effort to bring about such a change. We rank him among the Slovenian pioneers who strived for the teaching of philosophy, where the teaching of philosophizing is at the forefront. However, for this to succeed, we need a more radical change in social and economic circumstances. Without it, philosophizing turns into an interesting didactic game, and the changes in consciousness and behaviour that this game brings are merely fleeting and mostly disappear in time.